ASSESSING THE IMPACT OF A NEWLY INTRODUCED ELECTRONIC PRESCRIBING SYSTEM ACROSS A PAEDIATRIC DEPARTMENT – LESSONS LEARNED. Issue 9 (17th August 2016) - Tsyben, Anastasia; Gooding, Nigel; Kelsall, Wilf
Abstract : Aim: Prescribing audits have shown that the Women's and Children's Directorate reported higher number of prescription errors on the paediatric and neonatal wards compared to other areas in the Trust. Over the last three years a multidisciplinary prescribing team (PT), which included senior clinicians, pharmacists and trainees introduced a number of initiatives to improve the quality of prescribing. Strategies included structured departmental inductions, setting up of designated prescribing areas and reviewing errors with the prescriber. Year on year there were fewer prescribing errors.1 With the introduction of a new electronic prescribing system in October 2014 prescribing error rates were expected to decrease further, eradicating omissions around allergy recording, ward location and drug names. The aim of this abstract is to highlight the impact of the new system and describe lessons learned. Method: In the summer of 2014, all inpatient drug charts across the department were reviewed on three non-consecutive days over a period of three weeks. Prescribing errors were identified by the ward pharmacist. Errors were grouped according to type and further analyzed by the PT. Errors deemed to have no clinical significance were excluded. Error rates were compared to the previous audits performed with identical methodology. Following the introduction of the electronic prescribing system, the ward pharmacists continued to review prescription charts on daily basis and generate regular error reports to notify the staff of new challenges. Results: There were 174 (14%) errors out of 1225 prescriptions on 181 drug charts. The most commonly made mistakes included drug name errors, strength of preparation, allergies and ward documentation, prescriber's signature omissions, and antibiotic review and end dates. The introduction of an electronic system has eliminated drug name, strength of preparation, allergy recording and ward errors. However, serious challenges have been identified: entering of an incorrect weight resulted in all drug dosages being inaccurate; the timing of drug levels for Vancomycin and Gentamicin and the administration of subsequent doses have been problematic. Communication difficulties between all staff groups has led to dosage omission, duplicate administration and confusion around start and stop dates. The ability to prescribe away from the bedside and indeed the ward has compounded some of these problems. Conclusion: The implementation of a new electronic system has reduced prescribing errors but has also resulted in new challenges, some with significant patient safety implications. The lessons learned and good practice introduced following previous audits of "traditional paper based" prescribing are equally important with electronic prescribing. Communication between staff groups is crucial. It is likely that the full benefits of the system will be realized a year after its introduction. On-going audit is required to assess the impact and safety of the electronic prescribing and lessons learned.